Morphological characterization of Sapota (Manilkara zapota) germplasm (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An experiment was conducted to evaluate the morphological characterization of five germplasm of Sapota namely BAU Sapota-1, BAU Sapota-2, BAU Sapota-3, Deshi Sapota and Vietnam Sapota. Randomized complete block design with three replications was performed for investigating the morphology of Sapota. Results indicate that the tallest plant was Deshi Sapota and the shortest plant was BAU Sapota-2. Also, the highest stem circumference was found in Deshi Sapota which was 52.25 cm. The maximum spreaded plant both in north-south and east-west direction was found in BAU Sapota-1 which was 1.62 and 1.53 m, respectively. Maximum shoot girth was found in BAU Sapota-3 and BAU Sapota-1 plants showed the most vigorous growth whereas BAU Sapota-3 had the longest shoot length. Results revealed that significant difference (p